Life after Methyl Bromide: Research on 1,3-Dichloropropene plus Chloropicrin in Florida - Bielinski M. Santos (EDIS, 2008)
HS1119, a 7-page article by Bielinski M. Santos, summarizes the most important findings on 1,3-D + Pic research in Florida. Includes reference list. Published by the UF Department of Horticultural Sciences, October 2007.